REGIONAL LANGUAGE BACKGROUND AND STUDENTS’ COMMUNICATION STYLES IN A MULTICULTURAL CAMPUS CONTEXT - Dian Pratiwi Tumari; Salsabillah R. Bahsoan; Silfanna J. Podungge; Muziatun Muziatun (Jurnal Review Pendidikan dan Pengajaran, 2026)
Language is a crucial element in communication used to express ideas and maintain social relationships. Politeness strategies (Brown & Levinson, 1987) play an essential role in protecting the interlocutor's "face" and avoiding conflict, particularly within university academic environments. (Lakoff, 2004; Holmes, 1995) indicate that women tend to use more polite language compared to men, research exploring gender-based differences in politeness strategies at Universitas Negeri Gorontalo (UNG), This study examines politeness strategies and gender differences among English Department students at Universitas Negeri Gorontalo.  Drawing on Brown and Levinson's politeness theory, the study examines four strategies: bald on-record, positive politeness, negative politeness, and off-record. This research employed a qualitative descriptive design involving ten English Department students, consisting of five male and five female participants from the 2024 and 2025 cohorts. The data were collected through individual online interviews and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that positive politeness was the most frequently used strategy, followed by negative politeness and bald on-record strategies, while off-record strategies did not appear in the data. Female participants tended to use more positive and negative politeness strategies, whereas male participants used more direct forms in some situations. However, these differences should be interpreted cautiously because the study involved a small number of participants. The study suggests that politeness in student interaction is shaped not only by gender, but also by context, social distance, and communicative purpose.